The genetics of resistance to infectious pancreatic necrosis virus in rainbow trout unveiled through survival and virus load data - Ahmad, Aqeel; Aslam, Muhammad Luqman; Evensen, Øystein; Gamil, Amr A. A.; Berge, Andreas; Solberg, Thoralf; Schmitt, Armin Otto; Gjerde, Bjarne (Frontiers in Genetics, 2024)
Infectious Pancreatic Necrosis virus (IPNV) is one of the major threats to the animal welfare and economy of the rainbow trout farming industry. Previous research has demonstrated significant genetic variation for resistance against IPNV. The main objective of the study was to investigate the genetic architecture of resistance against IPNV in rainbow trout fry. To achieve this, 610 rainbow trout fry, from a full factorial mating between 5 sires and 5 dams, were bath challenged with the IPNV isolate (IPNV-AS) from Atlantic salmon reared at a commercial farm. The resistance against IPNV was accessed using three different phenotypes; binary survival (BS), total days survived (TDS) and virus load (VL) recorded on the fish throughout the 40-day challenge test. All fish were genotyped using a 57K Affymetrix SNP array. The IPNV-AS isolate resulted in an overall mortality of 62.1%. The heritability estimates for survival (BS h2 = 0.21 ± 0.06, TDS h2 = 0.25 ± 0.07) and VL traits (h2 = 0.23 ± 0.08) were moderate and indicative of potential use of selection for increased resistance to IPNV in rainbow trout selective breeding programs. The unity estimated genetic correlation between the two survival traits (BS and TDS) indicates that the traits can be considered the same trait. In contrast, a moderate favourable negative genetic correlation was found between VL and the two survival traits (−0.61 ± 0.22 to −0.70 ± 0.19). The GWAS of the traits with many QTLs crossing the chromosome-wide Bonferroni corrected threshold indicates the polygenic nature of the studied traits. Most of the 10 possible identified genes were found to be linked with immunity or viral pathogenesis, which could be potentially responsible for the significant genetic variation in survival against the IPNV-AS. The QTL validation analysis revealed no significant difference in the mortalities and VL among the three genotypes of the detected QTL. The VL trait showed larger variation among the dead fry and with a concordant pattern with the two survival phenotypes, but with no significant difference in the proportion of IPNV VL positive samples in the dead and the survived fry. Overall, the results indicate the polygenic nature of the studied traits and support the use of genomic selection to improve resistance against IPNV in rainbow trout breeding companies.